The Umkm Banana Chips Analisis Faktor-Faktor Keberhasilan Dalam Pengembangan Usaha Keripik Pisang Lumer (Studi Kasus Umkm Keripik Pisang Di Desa Pucangsari Kecamatan Purwodadi ) - Aji, Teguh Sarwo; Kodir, Abdul (Universitas Panca Marga, 2024)
Micro, Small and Medium Enterprises (UMKM) are one of the important pillars of the Indonesian economy. MSMEs play a significant role in creating jobs, increasing people's income, and supporting national economic growth. One form of UMKM that has quite potential and is very popular with the public is the banana chips business. The melted banana chips innovation is a development of traditional banana chips by adding melted chocolate sauce, providing a unique and interesting taste sensation. The research objective in analyzing the success factors of the banana chips business is to analyze the influence of internal and external factors on the success of developing the banana chips business using the SWOT matrix. And Analyze the appropriate and influential factors for BMC recommendations in developing the banana chips business. The research location was carried out in Pucangsari village, Purwodadi subdistrict using qualitative methods. Qualitative methods are research approaches that focus on collecting and analyzing non-numerical data, such as words, images, or objects, to understand concepts, opinions, or experiences. This research can use survey methods to collect data from banana chips business actors, in-depth interviews with industry stakeholders, and secondary data analysis from previous studies. Research results Based on the SWOT matrix, the influencing factor in developing the banana chips business is the product diversification strategy using strengths to face various threats. Improving product quality so that it can compete with similar products already circulating on the market (S1, T1, T3), Promoting product excellence to increase consumer buying interest (S3, S4, S5, T1, T2), Maintaining product price stability so that it is affordable and attractive increasing consumers (S2, T2), Establishing partnerships with banana farmers and traders to provide quality raw materials at stable prices (S1, S2, T4). The appropriate strategy in developing a banana chips business is to implement 9 BMC components starting from determining the value offered (value proposition) which has distinctive characteristics and product advantages, selecting the right consumer segment through market survey activities, implementing sales strategies and appropriate promotion to attract consumer buying interest (customer relationship), utilize resources (key resources) both human resources, capital and raw materials in accordance with business needs, carry out hygienic production activities (key activities) and maintain product quality, provide convenience for product can be distributed quickly to buyers (channel), calculate capital requirements correctly (cost structure), identify business partners (key partners) correctly and identify opportunities for revenue sources correctly (revenue stream).